If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying rx + sx + -1t = 1 Solving rx + sx + -1t = 1 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1sx' to each side of the equation. rx + sx + -1sx + -1t = 1 + -1sx Combine like terms: sx + -1sx = 0 rx + 0 + -1t = 1 + -1sx rx + -1t = 1 + -1sx Add 't' to each side of the equation. rx + -1t + t = 1 + -1sx + t Combine like terms: -1t + t = 0 rx + 0 = 1 + -1sx + t rx = 1 + -1sx + t Divide each side by 'x'. r = x-1 + -1s + tx-1 Simplifying r = x-1 + -1s + tx-1 Reorder the terms: r = -1s + tx-1 + x-1
| Y=1/20X | | (-8y^(3/4)/y^3z^6)^(-1/3) | | N+(n+2)=66 | | -3x-y=-6 | | (2x+20)-(x-14)=90 | | 17-(4x-2)=2(x+3) | | x-20+75+50=180 | | 1/2(2k-4)=3(k+2)-2k | | 4x^3-6x^2-5x+2=0 | | 75=-20+19g | | 2x^2-42x+245=0 | | 6b-8=4b | | 9x+2y=17fory | | 3/10x=-1 | | y/8-3=6 | | 90+x+5+2x-23=180 | | 28=x/9+7 | | -4m-24+2m=3m+6 | | 180=3x+60(x+20) | | 3S-5=4 | | 21=x/3+8 | | -11+k/4=-17 | | 3q^2-18q+15=0 | | 8y-5=-2y+75 | | (3/3+2/3)j=15 | | -5+7x=-33 | | k-20=9k-4 | | 2(8a-7)(a-5)=0 | | 2(8a-7)(1-5)=0 | | 3.7+10=8.49 | | -10b-29=-18b+91 | | 7(x+2)+7=3x+4(4+x) |